Thysanoptera in a vineyard agro-ecosystem in Piedmont (Bollettino di zoologia agraria e bachicoltura, 2024)
Thysanoptera communities present in a vineyard agro-ecosystem in Piedmont,Northern Italy, were studied. Samples were taken mainly from two vineyardsdudng 1991 and 1992. Samples of the vine and of the spontaneous flora werecollected taking different organs individually: leaves, flowers, bark as well as turfand litter. The environment is characterised by a well-diversified vegetation.Samples of 55 plant species have been collected, 12 of those are woods or shrubsand 43 herbaceous. Thysanoptera community consists of 44 species. Two of them, Thrips albopilosus Uzel and T. hukkineni Priesner, are new to the Italian fauna.This Thysanoptera fauna can be subdivided in 6 minor communities (both phyllophilousand anthophilous living on crops, trees and weeds). All of them exceptthe phyllophilous herbaceous one have a rich, typical and well-diversified composition.The phyllophilous ones are the most diverse. T. tabaci is the only speciesthat is dominant in almost all the habitats. T. major is abundant on grape flowersand on tree leaves and flowers. Thrips fuscipennis is very important on woodleaves and vine leaves and flowers. Chirothrips manicatus and Ceratothrips friciare dominant species on grass and Dycots flowers respectively and Drepanothripsreuteri on grape leaves. There are important interactions among the differentenvironments. T. major and T. fuscipennis move between the arboreous flora andthe vines. T. tabaci breeds on weeds in spring and in summer moves to vines andtrees. Predatory thrips often move from spontaneous vegetation towards vineyardstao. Overall positive influences of wild flora on the agro-ecosystem are prevalent.
Keywords: Vineyard; agro-ecosystem; Thysanoptera; community; diversity; interaction